Advertising Campaign Strategy Based on The Communication Objective: A Case Study at Tokobagus Advertising Campaigns (2011-2014) - Oscario, Angela; Kuntjara, Hagung; Adhityatama, Agus (Bina Nusantara University, 2016)
Article focused on advertising as one of the most important parts of marketing communication in one of the online shop, TokoBagus. Advertising communicated a message from a certain brand to the target audience through a particular medium. The aim of this research was making advertising with a powerful message, so it was able to become a captain of consciousness that could play an important role in economic and social systems of modern society. Because of its potential power, the creative advertising workers had a big responsibility in their hands. It was not only to explore the creativity visually or verbally to a creative worker, but also, they should understand the purpose of communication, the communication strategy, and the creative strategy. In this case, TokoBagus run this in making advertisement campaign to promote its brand. The method used in this research was the qualitative method and inductive model. Data were collected through an interview, literature, and visual data. Those collected data were analyzed using a qualitative-verificative strategy and case study method. The case study was Toko Bagus advertising campaign from the year 2011 to the year 2014 when finally its name changes into OLX. It finds that the advertisements only become beautiful works of art, but it does not solve the problem of the brand. Therefore, this research is important to document the communication strategy and the creative strategy of an advertising campaign so it can be a reference for a young designers or students.